A Critical Review of Herbs for Geriatric Women. - Sharma, Kusum; Purohit, Divya Raj; Sharma, Ishwar Dutt; Meena, Ankita; Neelima, A (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda links menopause with ageing. Ageing is a Vata predominant stage of life. In Ayurvedic texts, Aacharya Sushruta has described it is a normal physiology. And hence no any specific treatment is mentioned for the same. Geriatric care includes the promotion of health and longevity and management of diseases occurring in old age. It is also concerned with sustained, comfortable and healthy ageing. Thus, geriatric care has to address to two-fold problems, firstly the basic anti ageing care to retard the rate of physiological ageing and secondly the medical management of diseases and disorders specifically occurring in the old age such as heart discomfort, sleep disturbances, mood swings, irritability, Anxiety, physical and mental exhaustion, bladder problems, vaginal dryness, joint and muscular disorders. Hence geriatric care wants management of Agni, Bala, Dosha and Oja. Oja is responsible for Bala and much important processing for ageing. various researches have been reviewed for herbs in geriatric care and found that in Many herbs mentioned in texts which are used for prolongation of Ayu along with increase in Medha and Bala and to arrest the process of ageing i.e., Vaya sthapana Gana, Jivneeya Gana, Shatavari, Ashwagndha, Guduchi, Aamlaki. Most of the Dravya’s are Medhya, Rasayana and Balya among them which can be useful in management of geriatric women.